"We are chosen": bearing witness in Animal Parade. Issue 2 (3rd April 2019) - Polanco, Raquel
ABSTRACT: In this response to Chris Collins's Animal Parade I grapple with my personal, as well as a larger disciplinary reticence to adopt posthumanist perspectives. I argue that Animal Parade puts our disciplinary values on display and points to the unique position of the performance studies scholar-artist for addressing extinction, environmental destruction, and our relationship with non-human others. Specifically, I draw upon Benjamin Haas's notion of hopeless activism to articulate the way Animal Parade calls upon its audience and the performance studies scholar to bear witness in the Anthropocene.